BANKRUPTCY FORUM SHOPPING: THE UK AND US AS VENUES OF CHOICE FOR FOREIGN COMPANIES. Issue 4 (23rd September 2014) - McCormack, Gerard
Abstract This paper critically evaluates 'forum shopping' possibilities offered by the UK and US in bankruptcy/insolvency cases. While recognizing that in some quarters forum shopping has a bad name, the paper makes the point that strategic manoeuvring and transaction planning is what litigation and case management is all about. Certain countries are popular as forum shopping venues because of substantive law or the procedural advantages brought about by litigating in that country. The paper concludes that while the UK may have shut its doors too firmly against foreign forum shoppers, the US is too much a safe haven. The paper calls for a measure of jurisdictional restraint through raising entry barriers. While a bit of jurisdictional competition in insolvency law-making may be no bad thing, the US approach runs the risk of undermining important policies considered important by other countries such as the protection of employees and the public purse. It is also asymmetrical in that US bankruptcy jurisdiction is assumed in situations where, if foreign countries had acted on a similar basis, US recognition of the foreign proceedings would be denied.